Therapeutic Efficacy of E-64-d, a Selective Calpain Inhibitor, in Experimental Acute Spinal Cord Injury. (9th July 2015) - Zhang, Zifeng; Huang, Zheng; Dai, Hao; Wei, Licheng; Sun, Songtao; Gao, Feng
Abstract : This study aims to investigate the therapeutic effect of calpain inhibitor E-64-d on SCI and to find a new approach to treat SCI. When an SCI rat model was established, it was immediately administered with E-64-d. RT-PCR and Western blotting were used to determine the protein and mRNA levels of calpain 1 and 68-kD NFP. TUNEL staining and NeuN labeling were performed to analyze neuronal apoptosis in the lesion. Immunohistochemistry assay was carried out to observe the expressions of calpain 1 and GFAP. Cyclooxygenase-2 activity was measured to show the immune response status. Locomotor function was evaluated by inclined plane test and Basso, Beattie, and Bresnahan locomotor rating scale. The results showed that calpain 1 was activated after SCI occurred. Treatment with E-64-d decreased expressions of calpain 1 and GFAP, alleviated neuronal apoptosis, inhibited cyclooxygenase-2 activity, and resulted in the promoted locomotor function. Furthermore, combination of E-64-d and MP had better efficacy than did E-64-d or MP alone. E-64-d is expected to be applied to treat SCI, and its alliance with MP may provide a valid strategy for SCI therapy.